Sosialisasi dan Pelatihan Pembuatan Pestisida Nabati Dari Kulit Bawang Merah Bagi Masyarakat Dusun X Di Desa Lekis Rejo - Alrifky Jesen Melanza; Sinta Tasya Karisma; Desty Octa Zarona; Agelika Marsha Putra; Roby Agung Pratama; Umi Rahmawati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2026)
Students of the 2026 Baturaja University Real Work Lecture (KKN) carry out community service activities related to socialization and training in making plant-based pesticides. This program was carried out in Hamlet X, Lekis Rejo Village, with the main focus on education on making plant-based pesticides to local farmers and the surrounding community. The main problems faced by the community are the high volume of household organic waste that has not been managed properly, the high price of chemical pesticides for some small farmer groups and the habits of the community that still depend on it. Shallot peel (Allium Cepa L) is one of the most abundant wastes but is rarely used, even though onion peel waste contains active compounds such as saponins that function as repellents such as ants (Formicidae), crickets (Gryllus bimaculatus), mealybugs (Paracoccus Marginatus), aphids (Aphids), and armyworms (Spodoptera Litura). Therefore, there is a need for socialization and training related to the processing of organic waste from onion peels into effective vegetable pesticides. The results of the activity show that the community can make plant-based pesticides that are not only able to reduce organic waste but also as environmentally friendly pest control that supports sustainable agriculture.